A service evaluation of cough reflex testing to guide dysphagia management in the postsurgical adult head and neck patient population. Issue 3 (June 2016) - Holmes, Samantha
Abstract : Purpose of review: The article reviews recent literature supporting the use of cough reflex testing (CRT), and outlines a service evaluation of CRT conducted with postsurgical head and neck cancer patients. There is a growing evidence base to support the use of CRT in dysphagia management to establish laryngeal sensation and screen for silent aspiration; however, there is a lack of evidence relating to using CRT within the head and neck population. Recent findings: Over a 3-month period, inpatients on an ear, nose and throat/maxillofacial ward underwent CRT as part of their clinical swallow evaluation. Data from these patients were collected, including their diagnoses, CRT findings, and subsequent management. The evaluation was limited by difficulties in maintaining a supply of citric acid, accessing medics to prescribe the citric acid, and staffing levels, as administration of the CRT initially required two members of staff to be present. Summary: The service evaluation findings, alongside current evidence examining noncancer mortality rates, suggests identification of silent aspiration is important in this population. CRT was useful to rationalize instrumental assessments and was easily incorporated into the swallowing evaluation. More evidence is needed to support the use of CRT within the head and neck population.